Site Analysis Terhadap RTH Depan Stadion Panglima Sentik Kabupaten Penajam Paser Utara sebagai Pengembangan Taman Aktif - Dwi Nur Rohman; Nadia Almira Jordan (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
Green open space is an open space that contains plants, plants and vegetation to support ecological, socio-cultural and architectural benefits that can benefit the community. As mandated by the North Penajam Paser Regency government through the 2013-2033 RTRW, the minimum area of ​​green open space is 30% of the total area of ​​the district. The total area of ​​green open space that already exists in North Penajam Paser Regency is 46,814 Ha where this right is still less than the mandated area of ​​5,420 Ha. One of the green open spaces in Penajam Paser Utara Regency is the RTH in front of the Panglima Sentik Stadium which has an area of ​​6.3 hectares which has been built since 2016, but since it was built this green space tends to be neglected. Therefore, a site analysis was carried out to determine the current condition of the site to facilitate the development of the site in the future potential and problems of the site as well as the tendency of area development on the site